2022
DOI: 10.1038/s41375-022-01686-y
|View full text |Cite
|
Sign up to set email alerts
|

A senescence stress secretome is a hallmark of therapy-related myeloid neoplasm stromal tissue occurring soon after cytotoxic exposure

Abstract: Therapy-related myeloid neoplasm (tMN) is considered a direct consequence of DNA damage in hematopoietic stem cells. Despite increasing recognition that altered stroma can also drive leukemogenesis, the functional biology of the tMN microenvironment remains unknown. We performed multiomic (transcriptome, DNA damage response, cytokine secretome and functional profiling) characterization of bone marrow stromal cells from tMN patients. Critically, we also compared (i) patients with myeloid neoplasm and another ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…The WHO has grouped t-MN with secondary MN and renamed it as “myeloid neoplasm post cytotoxic therapy”, with the assertion that a majority of MDS and AML occurring post-cytotoxic therapy have TP53 mut and that only multi-hit TP53 mut had a poorer outcome compared to single-hit [ 2 , 18 ], thus undermining the poor prognosis of single-hit TP53 mut t-MN. Exclusion of single-hit TP53 mut t-MDS from the TP53 mutated MDS have huge impact on management such as consideration for allogeneic stem cell transplantation [ 34 ], and exclusion from clinical trials targeted toward TP53 mut MDS. For example, allogeneic SCT may not be offered to fit single-hit TP53 mut t-MDS with BM blast 5–9% (according to ICC) and <20% (according to WHO) as they are considered to have OS similar to TP53 wt MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has grouped t-MN with secondary MN and renamed it as “myeloid neoplasm post cytotoxic therapy”, with the assertion that a majority of MDS and AML occurring post-cytotoxic therapy have TP53 mut and that only multi-hit TP53 mut had a poorer outcome compared to single-hit [ 2 , 18 ], thus undermining the poor prognosis of single-hit TP53 mut t-MN. Exclusion of single-hit TP53 mut t-MDS from the TP53 mutated MDS have huge impact on management such as consideration for allogeneic stem cell transplantation [ 34 ], and exclusion from clinical trials targeted toward TP53 mut MDS. For example, allogeneic SCT may not be offered to fit single-hit TP53 mut t-MDS with BM blast 5–9% (according to ICC) and <20% (according to WHO) as they are considered to have OS similar to TP53 wt MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a more nuanced model has emerged: a preleukemic clone may exist before the exposure to DNA-damaging therapies [ 59 ] and persist thereafter without manifesting as t-MN [ 60 ]. In addition, the role of non-HSC factors such as mesenchymal stromal cells has been described [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the role of senescent stromal cells as an accomplice in the growth of a variety of epithelial-derived solid tumors [ 52 , 99 , 100 ]. Similarly, recent studies have shown that senescent mesenchymal stromal cells contribute to the development of myeloid tumors [ 101 , 102 , 103 , 104 ]. The positive effect of the senescent stroma on tumor progression has been well established, but behind the scenes are the molecular mechanisms that link senescent stroma, cancer cells, and the TME.…”
Section: How Senescent Stroma Promotes Tumor Progressionmentioning
confidence: 96%